Reactive arthritis and other musculoskeletal symptoms associated with acquisition of diarrhoeagenic Escherichia coli (DEC). Issue 5 (16th March 2020) - Tuompo, Riitta; Lääveri, Tinja; Hannu, Timo; Pakkanen, Sari H; Kirveskari, Juha; Leirisalo-Repo, Marjatta; Kantele, Anu
Abstract : Objectives: Using a prospective research design, we evaluated the association between acquisition of diarrhoeagenic Escherichia coli (DEC) and development of reactive arthritis (ReA) and other reactive musculoskeletal (MSK) symptoms among international travellers. Methods: A total of 526 study participants were asked to provide pretravel and post-travel stool samples and fill in questionnaires (pretravel, post-travel and 3-week follow-up). A multiplex quantitative PCR assay was deployed to detect five DEC comprising enteroaggregative E. coli, enteropathogenic E. coli, enterotoxigenic E. coli, enterohaemorrhagic E. coli and enteroinvasive E. coli and Salmonella, Shigella, Campylobacter, Yersinia, and Vibrio cholerae . Multivariate analysis was employed to identify factors predisposing to MSK symptoms. New post-travel MSK symptoms reported by participants with DEC were assessed by phone interviews and, if needed, clinically confirmed. Results: From among the total of 224 volunteers who returned all questionnaires and stool specimens, 38 (17.0%) reported MSK symptoms. Multivariate analysis revealed that acquisition of DEC was associated with MSK symptoms (OR 3.9; 95% CI 1.2 to 13.3). Of the 151 with only-DEC, four (2.6%) had ReA, two (1.3%) reactive tendinitis and three (2.0%) reactive arthralgia. ReA was mostly mild, and all patients with ReA were negative for human leucocyte antigen B27. Antibiotic treatment of travellers' diarrhoea did not prevent development of MSK symptoms. Conclusion: A total of 17% of volunteers reported post-travel MSK symptoms. DEC acquisition was associated with an increased risk of developing them, yet the ReA incidence remained low and the clinical picture mild. Antibiotic treatment did not protect against development of MSK symptoms.